NEUTRALIZATION AND ADDITION OF SWEETENING EFFECT IN PHYSICOCHEMICAL MICROBIOLOGICAL AND SENSORY PROPERTIES OF BUFFALO MILK AREQUIPE - ANDRADE P., Ricardo D.; VÉLEZ H., Grabiel I.; ARTEAGA M., Margarita R.; DÍAZ Q., Yolanda S.; SÁNCHES S., Saudit S. (Vitae, 2009)
The buffalo milk due to its composition, especially in carbohydrates, present a favorable aptitude for the elaboration of arequipe. Its milky product yield is 40% superior to bovine milk. This investigation evaluates the variation of two neutralization levels (0.09 and 0.10% lactic acid) and three sweeteners percentage (25% sucrose; 22% sucrose and 30% inverted sugar; 20% sucrose and 30% sugar inverted) in the elaboration of buffalo milk arequipe. The panel selected treatment was to test the satisfaction degree by measurement total solid contents, humidity, ashes, protein, fat, viscosity, colour, mesophiles, fecal coliforms, mushrooms and yeasts and Staphylococcus, coagulase positives. It is stored to room temperature, and microbiologicalanalyses are carried for mushrooms and yeasts, organoleptic (sandiness) and physicochemical (solid totals and humidity) by ten days intervals during sixty days. The selected treatment, with a confidence level of 95% is of 0.10% lactic acid, 20% sucrose and 30% inverted sugar. Arequipe presents total solid contents, humidity, ashes, protein and fat of 77.90 ± 0.04%; 22.10 ± 0.04%; 1.76 ± 0.09%; 9.85 ± 0.37% and 7.95 ± 0.41% respectively; a pseudoplastic and thixotropic behavior. Arequipe elaborated, in agreement with the microbiological analyses, comply with practical standards Colombian NTC 3757 of 1996 and conserves its microbiological, organoleptic and physicochemical characteristics until day fifty.